The Role of In-service Training Courses to Improve the Effectiveness of Human Resources in Anticipation of Zabol University of Medical Sciences - Mohammad Ghasemi (Journal of Global Pharma Technology, 2017)
Nowadays, increasing the efficiency of organizations depends upon the enhancement of efficiency of human resources. Eenhancing the efficiency of human resources in order to do things successfully, also depends on training, expansion of knowledge and skill as well as developing desirable behaviors. This study aimed at investigating the impact of training programs of development plan and promotion on the improvement of employees’ effectiveness. Participant s of the study includes 550 of the personnel of Zabol University of Medical Sciences. A researcher-made questionnaire was used as the research instrument which was designed based on Likert model. It is to be mentioned that the validity of the questionnaire was confirmed by expert supervisors and reliability was examined and approved through applying Cronbach alfa. Data analysis was done through applying SPSS, Kolmogorov-Smirnov, Pearson simple and multiple regression along with descriptive methods to test research variables. The results of the study indicated that training programs of development plan and promotion have significant impact on the improvement of employees’ effectiveness and its components such as job identifying, responsibility, management ability, and improvement of mutual relations.Keywords:  Effectiveness, Job identifying, Employees’ responsibility, Management ability, Improvement of mutual relations.